Functional roles of two novel P450 genes in the adaptability of Conogethes punctiferalis to three commonly used pesticides - Yuan, Xingxing; Li, Han; Guo, Xianru; Jiang, He; Zhang, Qi; Zhang, Lijuan; Wang, Gaoping; Li, Weizheng; Zhao, Man (Frontiers in Physiology, 2023)
Insect cytochrome P450 (CYP450) genes play important roles in the detoxification and metabolism of xenobiotics, such as plant allelochemicals, mycotoxins and pesticides. The polyphagous Conogethes punctiferalis is a serious economic pest of fruit trees and agricultural crops, and it shows high adaptability to different living environments. In this study, the molecular characteristics and expression patterns of two novel CYP genes, CYP6CV1 and CYP6AB51, were studied and analyzed using molecular cloning and quantitative real-time PCR. The CYP6CV1 and CYP6AB51 genes were expressed throughout various C. punctiferalis larval stages and in different tissues. Their expression levels increased along with larval development, and expression levels of the two target genes in the midgut were significantly higher than in other tissues. After treating with different concentrations of chlorantraniliprole, emamectin benzoate and lambda-cyhalothrin, independently, the relative expressions of the two target genes were significantly induced. To further study the functional roles of CYP6CV1 and CYP6AB51, the two target genes were silenced using RNA interference. After the dsRNA injection, the expression profiles of the two CYP genes were reduced 72.91% and 70.94%, respectively, and the mortality rates of the larvae significantly increased when treated with the three insecticides independently at LC10 values. Thus, CYP6CV1 and CYP6AB51 appear to play important roles in the detoxification of the three test insecticides in C. punctiferalis.